Water balance - stream water level from Röbäcksdalen Catchment, Sampling point 5 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2025)
Accurate measurements of the stream level of the main inflow and outflow of the lakes of SITES Water and streams within the research station catchment.
Röbäcksdalen Field Research Station (2025). Water balance - stream water level from Röbäcksdalen Catchment, Sampling point 5, 2020-10-26–2025-05-05 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/-DZt-uwgBfVRt6QpqFpzf3ag
Keywords: Röbäcksdalen Field Research Station; Stream; Time instant; Time instant; Stream level; Stream level; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap